Micro-Rheological Changes of Red Blood Cells in the Presence of an Arterio-Venous Fistula or a Loop-Shaped Venous Graft in the Rat - Szabo, Balazs; Tanczos, Bence; Varga, Adam; Barath, Barbara; Ghanem, Souleiman; Rezsabek, Zsofia; Al-Smadi, Mohammad Walid; Nemeth, Norbert (Frontiers in Physiology, 2020)
Introduction: In case of kidney failure hemodialysis is the primary kidney replacement technique. Several vascular access methods used for the therapy one of which is the arterio-venous fistula (AVF). In the AVF the blood flow is altered, which can elevate the mechanical stress on the red blood cells (RBC). This can affect the RBC hemorheological properties and it can further cause systemic changes. To lower the turbulence and shear stress, we performed a loop-shaped arterio-arterial venous interposition graft (loop-shaped graft) to compare its effect to the conventional AVF. Materials and Methods: Thirty male Wistar were used (permission registration Nr.: 25/2016/UDCAW). The animals were randomly divided into sham-operated, AVF and loop groups (n=10/each). The superficial inferior epigastric vein (SIEV) was used to create the AVF, and the loop-shaped graft. Blood samples were taken before/after the surgery and at the 1st, 3rd and 5th postoperative weeks. We measured hemorhelogical, hematological and blood gas parameters. The microcirculation of the hind limbs were also monitored, using Laser Doppler fluxmetry. Result: Hematocrit, RBC count and hemoglobin decreased by the 1st postoperative week. The erythrocyte aggregation values significantly increased in the fistula group by the 5th week (6.43±2.31 vs. 13.60; p<0.0001; vs. before operation). At the postoperative 1st week in the loop group, the values showed a significant decrease in RBC deformability. During the maturation period, dominantly at the 5th week, all values were normalized. The operated hind limb’s skin microcirculation significantly increased in the sham and loop group by the 1st week (39±10.57 vs. 73.93±1.97 BFU, p<0.01). This increase wasn’t observed in the fistula group probably due to a steal-effect. Conclusion: Unlike in the loop group, in the presence of the fistula several rheological parameters have changed. The loop-shaped graft had only minimal impact on micro-rheological parameters.